Análise da evoluç\~ao do acesso a serviços de TV por assinatura e de vídeos sob demanda no Brasil - Alexandre Ywata de Carvalho; Nícolas Nascimento Monteiro da Silva; Paulo C. Coutinho; André L. Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study analyzes the recent transformations in the consumption profile of audiovisual media services, transformations mainly marked by the intensive use of the internet. Such a phenomenon has reconfigured the strategies adopted by providers of traditional linear audiovisual media services, in response to the entry into the telecommunications market of non-linear segment companies, especially video-on-demand (VoD) service providers. The data used, all sourced from public databases, include the Continuous National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios Contínua - PNAD Contínua), the Family Budget Survey (Pesquisa de Orçamentos Familiares - POF), and the Information and Communication Technologies (ICT) Households survey (Tecnologias da Informaç\~ao e Comunicaç\~ao - TIC Domicílios) conducted by the Brazilian Internet Steering Committee (Comitê Gestor da Internet no Brasil - CGI.br). The objective is to present an overview of linear audiovisual media services, specifically subscription TV and VoD services. Furthermore, we conducted estimates to study the factors influencing consumption decisions and the substitution of subscription TV by VoD services, using the statistical technique called logistic regression.
Keywords: O33; O31; 330; video-on-demand; subscription TV services; logistic regression; public microdata